ECONOMICAL CORE AT THE DIFFERENT LEVELS OF MANAGEMENT SYSTEM HIERARCHY - К. В. Павлов (Ринкова економіка: сучасна теорія і практика управління, 2016)
The process of the developed market relations formation in Russia led to the emergence of many problems whose solution requires taking into account territorial specificities. Moreover, ignorance of the regional factors caused enough high inefficiency of market reforms transformation. Theoretically, regional economic policy seeks to optimize spatial structures of macroeconomic position as underestimation and disregard the more regional peculiarities of market relations negatively affect the overall economic situation in the country. In this regard, it should be noted that the allocation of regional growth poles and propulsive industries that are the most dynamic, contributes to the momentum for the development of economic processes: an increase in employment of human resources, operation of related industries. Thus, due to the unequal economic development always possible to distinguish propulsive industries that stimulates the development of the economy and represent poles of growth. Moreover, the process of concentration of production focuses propulsive field in a neighborhood that is usually called point center growth (such as Silicon Valley in the USA or Bangalore in India). The combination of economical cores of growth poles includes other elements. The formation of the economical core may cause two problems, such as the power pulse cannot be sent to areas that require support, and advanced on areas which are closely related economically propulsive industries that are also included in the growth pole; probable lack of resources (financial and human). In such circumstances, financial management becomes a priority. Reinvestment in poles of growth will promote synergetic effect and will lead not only to increased production in the region, but also to improve social indicators, improvement of living standards. Polarized growth impulses form of the production-territorial structure emanating from the poles of development, which are the centers of concentration of production. The impact of the poles depends on what they are and what kind of impulses from the overlook is: the development of industrial relations (technical polarization), expansion of market relations (monetary polarization), social attraction (psychological polarization). All three forms of influence center on the environment are interrelated, but their practical value unequal to different poles and even one center at different stages of development. Thus, having considered the concept of “propulsive sector” and “pole of growth” that appear in the scientific literature by various authors, we can assume that the poles of growth - the area where concentrated industries and are propulsive industry, and the main feature of growth poles is to promote the development of various elements of the economy. This propulsive industry is leading sectors characterized by maximum production volume, affecting the economy and has a dynamic. Thus, when selecting the optimal option we should use the core economic indicators characterizing the processes of concentration and specialization of production, as well as various expert methods. In addition, it is advisable to use an indicator of structural flexibility.